2017
DOI: 10.3310/phr05040
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Psychoactive Substances in the UK Project: empirical and conceptual review work to produce research recommendations

Abstract: BackgroundAlthough illegal drug use has largely been declining in the UK over the past decade, this period has witnessed the emergence of a range of novel psychoactive substances (NPS) (‘legal highs’). These are new, mostly synthetic, substances that mimic the effects of existing drugs). Despite there being many causes for concern in relation to NPS, there has been little prior study of the burden associated with their use in public health terms. Clarity is lacking on research priorities in this rapidly develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 701 publications
0
48
0
Order By: Relevance
“…The growing number of SCRAs on the global and national market, their chemical diversity, frequent changes in composition, and difficulties that come with the analysis of these substances pose a significant challenge for clinical toxicologists and forensic services. Routine analysis and screening of these substances in biological samples and seized materials mainly rely on the analytical methods such as GC/MS, HPLC/MS, and immunochemical assays (10,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of SCRAs on the global and national market, their chemical diversity, frequent changes in composition, and difficulties that come with the analysis of these substances pose a significant challenge for clinical toxicologists and forensic services. Routine analysis and screening of these substances in biological samples and seized materials mainly rely on the analytical methods such as GC/MS, HPLC/MS, and immunochemical assays (10,(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of schemes for controlling and regulating the supply of NPS have been devised and trialled around Europe. 23 None of these appear to have been completely successful although it is important to remain mindful of international best practice. 1 It is hoped that a reexamination of the effectiveness of the PSA after it has been in place for a more substantial period of time will reveal a sustained benefit to those a risk due to use of NPS.…”
Section: Resultsmentioning
confidence: 99%
“…Using a scoping review, Mdege et al 45 identified 995 articles, the majority of which examined the healthrelated adverse effects of NPS use at the individual level. They highlighted that the expanding literature on the NPS phenomenon is primarily clustered around four key areas:…”
Section: Deathsmentioning
confidence: 99%
“…46 They conclude that the literature is characterised by being early in its stage of development and lacking in data to directly inform an evidence-informed public health response to NPSs. 45 Regarding survey data, there are 29 identified studies that assessed NPS use prevalence in the UK. The authors usefully summarised the findings of the prevalence studies in tabular form.…”
Section: Deathsmentioning
confidence: 99%
See 1 more Smart Citation